TEACHERS' PERCEPTION ON WRITING ASSESSMENT BASED ON 2013 CURRICULUM AT MAN 2 KEDIRI - Pamungkas, Dewi Sari; Sulistyanto, Irwan (Faculty of Teacher Training and Education, English Department, UNISKA, Kediri, 2021)
This research is purposed to describe teachers’ perception on writing assessment based on 2013 curriculum at MAN 2 Kediri. This research used descriptive qualitative as the approach. The subject of this research is six English teachers of MAN 2 Kediri. There are two tools that were used to get the data namely questionnaire and interview. The results of this research are (1) in attitude assessment, almost all teachers of MAN 2 Kediri arrange the instrument in the right way, but the scoring rubric was not appropriate with 2013 curriculum (2) in knowledge assessment, all teachers of MAN 2 Kediri arrange the question and scoring rubric appropriately with 2013 curriculum (3) in psychomotor assessment, teachers arrange the question in psychomotor assessment in the right way but the choosing of question is not suitable for psychomotor assessment. For the scoring, all teachers use analytic rubric, but, do not concern the criteria in the scoring rubric. (4) most of teachers do not have any problems in the writing assessment. For the suggestions, teachers should add the description in scoring rubric for attitude assessment as the same with 2013 curriculum. Next, in choosing the question/task should be appropriate with the aspect that will be assessed. The last, teachers should determine the criteria for scoring rubric in knowledge and psychomotor assessment.